Contradictory Logics in Asset‐building Discourse: Habits, Identities and Discipline. (15th June 2017) - Feldman, Guy
Abstract: Asset‐building as an anti‐poverty policy emphasizes helping the poor to save and accumulate wealth so as to promote future financial well‐being. This article focuses on how asset‐building discourse is practiced at the frontlines and its implications for how workers come to address issues of poverty. Drawing on qualitative data from a case study of a matched savings programme in the USA, the study finds that asset‐building discourse as enacted by workers is fundamentally contradictory: it promotes the idea that the poor can acquire financial literacy, but simultaneously works to discipline the poor to thoughtlessly save out of habit. More priority is placed on inculcating the habit of saving rather than teaching economically rational decision‐making. These findings indicate that asset‐building is consistent with a neo‐liberal outlook that focuses on disciplining the poor to be market compliant irrespective of whether their participation in market‐based activities effectively addresses the challenges of living in poverty.